2021
DOI: 10.1101/2021.08.19.21262238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The WORC database: MRI and CT scans, segmentations, and clinical labels for 930 patients from six radiomics studies

Abstract: The WORC database consists in total of 930 patients composed of six datasets gathered at the Erasmus MC, consisting of patients with: 1) well-differentiated liposarcoma or lipoma (115 patients); 2) desmoid-type fibromatosis or extremity soft-tissue sarcomas (203 patients); 3) primary solid liver tumors, either malignant (hepatocellular carcinoma or intrahepatic cholangiocarcinoma) or benign (hepatocellular adenoma or focal nodular hyperplasia) (186 patients); 4) gastrointestinal stromal tumors (GISTs) and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…A recent study (dos Santos et al, 2021) even warned that radiomics research must achieve "higher evidence levels" to avoid a reproducibility crisis such as the recent one in psychology (Open Science Collaboration, 2015). Hence, to facilitate reproducibility, besides automating the radiomics workflows construction, we have publicly released six datasets with a total of 930 patients (Starmans et al, 2021c), and made the WORC toolbox and the code to perform our experiments on all datasets open-source (Starmans et al, 2018a;Starmans, 2021). Besides a lack of reproducibility, there is a positive publication bias in radiomics, with as few as 6% of the studies between 2015 and 2018 showing negative results as reported by Buvat and Orlhac (2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study (dos Santos et al, 2021) even warned that radiomics research must achieve "higher evidence levels" to avoid a reproducibility crisis such as the recent one in psychology (Open Science Collaboration, 2015). Hence, to facilitate reproducibility, besides automating the radiomics workflows construction, we have publicly released six datasets with a total of 930 patients (Starmans et al, 2021c), and made the WORC toolbox and the code to perform our experiments on all datasets open-source (Starmans et al, 2018a;Starmans, 2021). Besides a lack of reproducibility, there is a positive publication bias in radiomics, with as few as 6% of the studies between 2015 and 2018 showing negative results as reported by Buvat and Orlhac (2019).…”
Section: Discussionmentioning
confidence: 99%
“…The first six datasets (Lipo, Desmoid, Liver, GIST, CRLM, and Melanoma) are publicly released as part of this study, see (Starmans et al, 2021c) for more details. Three datasets (HCC, MesFib, and Prostate) cannot be made publicly available.…”
Section: Evaluation Of Default Configuration On Twelve Different Clin...mentioning
confidence: 99%
See 3 more Smart Citations